Effect of limited - creep feeding on performance of spring-born calves - Simms, D.; Kuhl, Gerry L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three limited-creep feeding trials were conducted with spring-born suckling calves on native grass. The 1696 crude protein, high energy creep feed containing Bovatec® was fed from mid-August to weaning in mid-October. Limited-creep feeding increased (P<.05) calf gains .19 lb per/head/daily with an average daily consumption of 2.15 lb, giving a creep feed-to-gain conversion rate of 11.2.
Keywords: Beef; Creep feeding; Calves; Performance